Analysis of Employee Performance Levels in the Commercial Operation Unit of PT. Angkasa Pura 1 I Gusti Ngurah Rai Airport Branch Office - Arimbawa, I Putu Angga; Gede, I Gusti Ketut; Marhaeni, Kadek Eni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
In a company, there are several factors that can make the company achieve its goals, one of which is human resources (HR), namely employees. Good quality human resources will have a good impact on the company and can encourage the company to move for the better. PT Angkasa Pura I (Persero) is a State-Owned Enterprise (BUMN) company which operates in the airport services business. Based on data, the total average absence for the last 6 months was 4.37%. Because it exceeds 3%, it is categorized as high. This means that the higher the level of employee absenteeism, the lower the level of employee performance. So, the aim of this research is to determine the level of employee performance and efforts to improve employee performance in the Commercial Operation Unit of PT. Angkasa Pura 1 I Gusti Ngurah Rai Airport Branch Office. The limitation of this research is only to determine the level of employee performance and efforts to improve employee performance. The analytical method used is a qualitative descriptive data analysis method.  Qualitative descriptive analysis can take the form of observations, interviews, or questionnaires. The results of the research are an analysis of employee performance levels at the Commercial Operation Unit of PT Angkasa Pura I I Gusti Ngurah Rai Airport Branch Office seen from the five indicators, namely work quantity, work quality, timeliness, work discipline and ability, showing that the employee's performance level can be said to be very good. , with a percentage of between 80%-100%. The indicator that has the highest percentage value of employee performance level is quality of 92%, while the indicator that has the lowest percentage value of employee performance is attendance of 89.50%.